Exchange rate regimes and foreign direct investment flow in West African Monetary Zone (WAMZ) - Perekunah B. Eregha (African Governance and Development Institute (AGDI), 2019)
This study examines the effect of exchange rate regimes on Foreign Direct Investment (FDI) flow for WAMZ. The Arellano Panel Correction for Serial Correlation and Heteroskedaticity option of the Within Estimator for fixed effect panel data model as well as the Dynamic Panel Data Instrumental Variable Approach by Anderson and Hsiao (1981) for the countries selected based on data availability for the period 1980-2016 were used. The fixed exchange rate regime was found to hamper FDI flow in the zone while intermediate policy had a significantly positive effect in facilitating FDI flow during periods of declining foreign reserves and narrowing current account balance in WAMZ. This implies that the transmission of the effect of exchange rate regimes on FDI inflows depends on the positions of the foreign reserves and current account balance in the zone. Consequently, the fixed regime is not a good policy in periods of narrowing current account balance and depleting foreign exchange reserves. The study therefore recommends the need for monetary authorities to be cautious in managing their exchange rates especially in periods of depleting foreign reserves and narrowing current account so as not to deter the much needed FDI inflow.
Keywords: E31; F21; F31; 330; Exchange Rate Regimes; Inflationary Expectation; Exchange rate uncertainty; Foreign Direct Investment Flow; Panel Data Analysis